Zinc ion‐induced formation of hierarchical N‐succinyl chitosan film. Issue 14 (10th April 2017) - Wang, Hongjiao; Liu, Shunli; Zhang, Aokai; Li, Kewen; Oderinde, Olayinka; Yao, Fang; Fu, Guodong
ABSTRACT: A series of N‐succinyl Chitosan (NSCS) hydrogel derived from different substitution degree of NSCS were fabricated through the zinc ions crosslinking. Subsequently, a light‐weight, transparent, and hierarchical NSCS‐Zn(II) film was obtained by drying the hydrogel. The hierarchical structure of NSCS‐Zn(II) film was confirmed by scanning electron microscopy. The NSCS‐Zn(II) film exhibited excellent mechanical strength because of the preferential formation of the alignment structure. The tensile strength and Young's modulus reaches 119.3 MPa and 2.67 GPa when the NSCS substitution degree was 91.95%. Furthermore, a remarkable and enhanced broad‐spectrum bactericidal properties of the NSCS‐Zn(II) film was revealed through E. coli and S. aureus exposure, respectively. These features indicated that NSCS‐Zn(II) film is a promising material that can be used in biomedical engineering. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44664. Abstract :